Sustainable development, climate change and energy trade in the regional context of MERCOSUR: considerations for Uruguay - Stuhldreher, Amalia; Morales Olmos, Virginia (Latin American Journal of Trade Policy, 2020)
Considering the diverse challenges of the current international environment, marked by uncertainty and various risks,but which also opens up opportunities for the Latin American region, this paper analyzes the search for articulation of energy policies, the situation regarding renewable energies in the context of MERCOSUR (Southern Common Market) and trade interms ofenergy, focusing on the case of Uruguay and its links with Argentina and Brazil. Based on a sustainable development perspective, the evolution of energy matrices and their eventual contributions in terms of climate change mitigation are reviewed. In this context, the process of investments in the renewable energy sector in Uruguay in recent years stands out, which have enabled exports from private actors since 2017. Consideringthe multidimensionality of development processes, the work explores some perspectives that arise from regional and national processes for the promotion of sustainable development models and the fight against climate change, including the complexity of the dialogue between the dimension environmental and economic-commercial dimension.